Co-administration of avian influenza virus H5 plasmid DNA with chicken IL-15 and IL-18 enhanced chickens immune responses - Lim, Kian-Lam (BioMed Central, 2012)
BACKGROUND: DNA vaccines offer several advantages over conventional vaccines in the development of effective vaccines against avian influenza virus (AIV). However, one of the limitations of the DNA vaccine in poultry is that it induces poor immune responses. In this study, chicken interleukin (IL) -15 and IL-18 were used as genetic adjuvants to improve the immune responses induced from the H5 DNA vaccination in chickens. The immunogenicity of the recombinant plasmid DNA was analyzed based on the antibody production, T cell responses and cytokine production, following inoculation in 1-day-old (Trial 1) and 14-day-old (Trial 2) specific-pathogen-free chickens. Hence, the purpose of the present study was to explore the role of chicken IL-15 and IL-18 as adjuvants following the vaccination of chickens with the H5 DNA vaccine. RESULTS: The overall HI antibody titer in chickens immunized with pDis/H5 + pDis/IL-15 was higher compared to chickens immunized with pDis/H5 (p < 0.05). The findings revealed that the inoculation of the 14-day-old chickens exhibited a shorter time to achieve the highest HI titer in comparison to the inoculation of the 1-day-old chickens. The cellular immunity was assessed by the flow cytometry analysis to enumerate CD4+ and CD8 + T cells in the peripheral blood. The chickens inoculated with pDis/H5 + pDis/IL-15 demonstrated the highest increase in CD4+ T cells population relative to the control chickens. However, this study revealed that pDis/H5 + pDis/IL-15 was not significant (P > 0.05) in inducing CD8+ T cells. Meanwhile, with the exception of Trial 1, the flow cytometry results for Trial 2 demonstrated that the pDis/H5 + pDis/IL-18 inoculated group was able to trigger a higher increase in CD4+ T cells than the pDis/H5 group (P < 0.05). On the other hand, the pDis/H5 + pDis/IL-18 group was not significant (P > 0.05) in modulating CD8+ T cells population in both trials. The pDis/H5 + pDis/IL-15 inoculated group showed the highest IL-15 gene expression in both trials compared to other inoculated groups (P < 0.05). Similar results were obtained for the IL-18 expression where the pDis/H5 + pDis/IL-18 groups in both trials (Table 8) were significantly higher compared to the control group (P < 0.05). However, the expressions of other cytokines remained low or undetected by GeXP assay. CONCLUSIONS: This study shows the diverse immunogenicity of pDis/H5 co-administered with chicken IL-15 and IL-18,with pDis/H5 + pDis/IL-15 being a better vaccine candidate compared to other groups.